BRAND AMBASSADOR AND BRAND IMAGE ON PURCHASING DECISIONS WITH WOM AS AN INTERVENING VARIABLE IN ONLINE SHOP SHOPEE ON COLLEGE STUDENTS IN KERINCI DISTRICT AND SUNGAI PENUH CITY: INDRA BUDAYA - Budaya, Indra (Qawwam : The Leader's Writing, 2024)
The aim of this research based on the problems above is to find out whether brand ambassadors and brand image have a positive and significant influence on e-WOM in decisions. The object of this research is all students in Sungai Banyak City and Kerinci Regency with a total of 50 respondents. The results of this research are that Brand Ambassadors have a direct influence on purchasing decisions as evidenced by the results of (0.001 < 0.05) and the calculated t value < t table (3.733 > 2.01063), Brand Image does not have a direct influence on purchasing decisions as evidenced by the results of 0.892 > 0.05 and t count < t table (0.137 < 2.01063), Brand Ambassador has no influence on WOM (Word Of Mouth) as evidenced by the results of 0.862 > 0.05 and t count < t table (0.345 < 2.01063), Brand Image has no influence on WOM (Word Of Mouth) as evidenced by the results 0.732> 0.05 and t count < t table (0.345 < 2.01063), WOM (Word of Mouth) has no influence on purchasing decisions as evidenced by the results of 0.140> 0.05 and t count < t table (1.503 < 2.01063).